Problematika Masyarakat Modern dalam Kumpulan Cerpen Tawa Gadis Padang Sampah Karya Ahmad Tohari - Achmad Sultoni; M. Lukman Leksono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the problems of modern society contained in the collection of short stories ‘Tawa Gadis Padang Sampah’ by Ahmad Tohari. The aim is to find out the forms of social problems in the collection of short stories ‘Tawa Gadis Padang Sampah’ by Ahmad Tohari. The data source of the research is the book collection of short stories Tawa Gadis Padang Sampah by social theme. This research is a descriptive qualitative research with a method of describing data in depth. Data is collected through the stages of reading short text carefully, classifying data, interpreting the results of data analysis, confirming the results of the analysis, and concluding the analysis results. The results of the study indicate that there are three forms of social problems of modern society that exist in the collection of short stories ‘Tawa Gadis Padang Sampah’ by Ahmad Tohari, including: poverty, environmental problems, and youth issues. Keywords: Short Stories, Social Problems, Sociology of Literature.